Interceding Role of Agricultural Extension Services in Adoption of Climate-Smart Agricultural Technologies in Northern Ghana - Anang, Benjamin Tetteh (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2022)
As a result of the effect of climate change on food security and rural livelihoods, the promotion and adoption of climate-smart agricultural practices have become very crucial. The role of agricultural extension in the adoption decision process is an important factor. However, extension delivery systems in most developing countries face numerous challenges that raise concerns about their ability to bring about the desired impact on farm households’ decisions. Relying on data from a cross-section of smallholder farmers in Ghana’s northern savanna area, specifically the Tolon district, the study assessed the determinants of farmers’ decision to adopt climate-smart agriculture (CSA) practices as well as the intensity of adoption and the role agricultural extension plays in CSA adoption. Using a Poisson regression with endogenous treatment effects model to account for selectivity bias, the study observed that farmers adopt multiple CSA practices, with adoption being influenced by farmer group membership, size of herd and participation in off-farm work. Intensity of adoption, on the other hand, increased with access to agricultural extension, farm credit and input subsidy, but decreased with farm size and participation in off-farm work. Furthermore, an impact assessment indicated that participants in agricultural extension had 1.27 more adoption of CSA practices than they would if they had not participated in agricultural extension. The study concludes that there is a strong association between adoption intensity and access to agricultural support services such as extension, input subsidy and agricultural credit. The interceding role of extension in the adoption of CSA practices calls for more resources to be channeled towards extension service provision as a means to mitigate the effects of climate change and promote sustainable production at the farm level. The positive externalities from CSA adoption will go a long way to protect the environment, promote food security and rural livelihoods.